Aristotelian Realism: Political Friendship and the Problem of Stability. Issue 4 (2019) - Cheng, Eric
Abstract: This paper argues that the pursuit of stability is the primary concern of Aristotle's understanding of political friendship. Specifically, I argue that Aristotle chooses to understand political friendship to be a "special sort" of utility/advantage friendship, applicable to multiple regime types of varying degrees of (in)equality, because he fears what might happen when citizens in any polity develop mutual animosity. Turning to the contemporary liberal democratic context, I note that Aristotle provides us with a strong positive argument for why we ought to take political friendship seriously. However, I stipulate that contemporary liberal democracies present obstacles to the realization of classical political friendship. I thereby conclude by suggesting that citizens can potentially be political friends when they understand politics and their social relations through the "metaphor" of political friendship.